69.6k views
5 votes
Simplify the expression. Write the answer using scientific notation. (9x10^2)(2x10^10)

2 Answers

5 votes

Answer:

1.8 x
10^(13)

Explanation:

( 9 x 10²) (2 x
10^(10) )

= (9)(2) x
10^(10+2)

=18 x
10^(12)

= 1.8 x
10^(13)

User BJ Clark
by
5.1k points
2 votes

Answer:

(9x10^2)(2x10^10)

= 1.9 x 10^13 (In scientific notation)

Explanation:

Expression to be simplified is given as:

(9x10^2)(2x10^10)

= 9x10^2x2x10^10

= 9x2x10^2x10^10

The base here in the expression is same so the power will add up:

= 18 x 10^(2+10)

= 1.8 x 10^12

Using Scientific notation on the expression, we know that the decimal point must after the first digit so that the number let us say x is such that x > 0 and x < 10. To move decimal one place back, we will multiply it with 10^1:

18 x 10^12

= 1.8 x 10 x 10^12

= 1.8 x 10^(1+12)

= 1.8 x 10^13

User Tch
by
4.3k points